1990
DOI: 10.1079/pns19900052
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous mediators of growth

Abstract: Growth comprises three separate componcnts; whole-body growth, tissue turnover and repair, and last, the response to external stimuli. Whole-body growth can be divided into changes associated with muscle, skin, viscera and skeleton. Because of our interest in bone metabolism the present review will concentratc on the processes associated with skeletal growth, turnover, and response to external stimuli. Although some of the factors which will be discussed are specific to bone the majority affect other body tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Additionally, it is known that physical training improves bone quality, ameliorating both mineral density and protein content (33). However, the benefits of physical training have to be supported by an adequate intake of protein, an important osteotrophic nutrient (7,(34)(35)(36); otherwise a negative nitrogen balance may be created, making it impossible for the osteoblasts to lay down the necessary organic matrix, which is the first step in the formation of bone (37). As such, our data demonstrate that 14% protein was not sufficient to maintain the potential of bone growth (36,38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is known that physical training improves bone quality, ameliorating both mineral density and protein content (33). However, the benefits of physical training have to be supported by an adequate intake of protein, an important osteotrophic nutrient (7,(34)(35)(36); otherwise a negative nitrogen balance may be created, making it impossible for the osteoblasts to lay down the necessary organic matrix, which is the first step in the formation of bone (37). As such, our data demonstrate that 14% protein was not sufficient to maintain the potential of bone growth (36,38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Having established that C2-ceramide inhibits proliferation and induces apoptosis, we went on to demonstrate that these effects are not mediated through the inhibition of the IGF-I signalling pathway, which is the major autocrine/paracrine regulator of bone growth (Loveridge et al 1990). Strle et al (2004) demonstrated that ceramide inhibits IGF-I-induced protein synthesis and differentiation in myoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…The IGF-I signalling pathway is the major autocrine/paracrine regulator of bone growth (Loveridge et al 1990). Binding of IGF-I to its receptor utilises a family of soluble receptors, known as insulin receptor substrates (IRSs), to initiate a series of autophosphorylation events.…”
Section: Introductionmentioning
confidence: 99%
“…The IGF-1 signalling pathway is unequivocally a major autocrine/paracrine regulator of bone growth [100]. Proinflammatory cytokines may modulate the IGF-1 signalling cascade at one or more junctures: IGF-1 receptor binding; insulin receptor substrate phosphorylation; the p44/42 mitogenactivated protein kinase (MAPK) signalling pathway; the phosphatidylinositol 3-kinase (PI-3K) signalling pathway; and Akt phosphorylation (Fig.…”
Section: Igf-1 Signallingmentioning
confidence: 99%